Use of Sodium Channel Blockers in the Thr226Met Pathologic Variant of SCN1A: A Case Report - Nájera-Chávez, Brenda Carolina; Seeber, Lea; Goldhahn, Klaus; Panzer, Axel (Neuropediatrics, 2023)
The Thr226Met pathologic variant of the SCN1A gene has been associated with the clinical development of an early infantile developmental and epileptic encephalopathy (EIDEE) different from Dravet's syndrome. The electrophysiological mechanisms of the mutated channel lead to a paradoxical gain and loss of function. The use of sodium channel blockers (SCB) that counteract this gain of function has been described in previous studies and they can be safely administered to patients carrying mutations in other sodium channel subtypes without causing a worsening of seizures. We report the use of SCB in a child harboring the Thr226Met pathologic variant of SCN1A with early-onset pharmaco-resistant migrating seizures, as well as developmental delay. Lacosamide led to a dramatic reduction in seizure frequency; however, only a mild improvement in the epileptic activity depicted by electroencephalography (EEG) was achieved. The introduction of carbamazepine as an add-on therapy led to a notable reduction in epileptic activity via EEG and to an improvement in sensorimotor development. Despite the overall clinical improvement, the patient developed febrile seizures and a nonepileptic jerking of the right hand. In this case of EIDEE with the Thr226Met variant, we demonstrate a beneficial pharmacological intervention of SCB in contrast to findings described in current literature. Our report encourages the cautious use of SCB at early stages of the disease in patients carrying this pathologic variant.
Keywords: SCN1A; Thr226Met; early infantile developmental and epileptic encephalopathy; sodium channel blocker; gain and loss of function; voltage gated sodium channel